PENINGKATAN KEMAMPUAN MENGHAFAL MATA PELAJARAN AL-QUR’AN HADITS MATERI SURAT PENDEK MENGGUNAKAN MEDIA HIDDEN CHART PADA SISWA KELAS IV SEMESTER II DI MI AL-IKHLASH SURABAYA - Sari, Intania Cahaya (Journal Of Islamic Elementary School (JIES), 2018)
The low ability to memorize students with a percentage of completeness of memorizing ability of 6.25% in the material memorizing short al-Insyirah letters at Al-Ikhlash MI Surabaya was the beginning of this research. The lack of variations in learning media and the unavailability of learning resources in the form of books makes learning less attractive and students tend to be passive. Based on this, it is necessary to improve learning that can improve the ability to memorize students in the subjects of the Qur'an Hadith. The solution to overcome these problems is through the use of hidden chart media with the aim of improving students' memorizing abilities. The objectives of this study are: 1) Knowing the application of hidden chart media in improving the ability to memorize short letters on Al-Qur'an Hadith subjects in the fourth grade of Al-Ikhlash MI Surabaya. 2) Knowing the increase in the ability to memorize short letters through hidden chart media on Al-Qur'an Hadith subjects in class IV of Al-Ikhlash MI Surabaya. This research was conducted using the Kurt Lewin model class action research method consisting of 2 cycles. Each cycle consists of 4 stages, namely planning (planning), action (acting), observation (observing) and reflection (reflecting). Data collection techniques consist of observation, interviews, performance and documentation. The results of the study show that: (1) The application of hidden chart media is said to be going well. Teacher activity in learning has increased, from 81.25% (good) to 93.75% (very good) in cycle II. The activities of students in the first cycle were 78.75% (good) which increased in the second cycle to 92.5% (very good). (2) The increase in the ability to memorize short letters gets a percentage of 6.25% (low) students who complete pre-cycle, 56.25% (less) students complete in the first cycle, and with a percentage of 81.25% (good) students completed in cycle II. based on the results of research on teacher activities, student activities, as well as the results of the ability to memorize material students memorizing short letters using hidden chart media produce changes in a better direction.